THE CHARACTERISTICS OF VICTIM OF DOMESTIC VIOLENCE AT RSUP DR. KARIADI SEMARANG PERIOD 2018 – 2022 - Naurah Qhalisa Raniah; Tuntas Dhanardhono; Sigid Kirana Lintang Bhima; Saebani Saebani (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Background: Domestic violence is an act of violence against someone , especially woman which results in physical, sexual, psychological misery or suffering, and/or domestic neglect that occurs in household scope. The incidents of domestic violence are very often found in society, including in Semarang, with a total more than 1.000 domestic violence cases recorded during 2018 – 2022. Even though the number recorded is quite large, only very few domestic violence cases processed to the legal realm. Proof of domestic violence cases can be seen through one of valid pieces of evidence, Visum et Repertum which include informations related to the characteristics of domestic violence victim. Objective: To find out characteristics of victim of domestic violence at RSUP Dr. Kariadi Semarang in 2018 – 2022. Methods: This type of research is a retrospectice descriptive study with cross-sectional study. The sample for this study was taken from the results of medical records and visum et repertum of victims of domestic violence recorded at the Results: According to 234 domestic violence cases recorded at RSUP Dr.Kariadi Semarang from 2018 to 2022, 2018 had the highest incident of domestic violence as many as 70 cases (30%) from the total. Victims were dominated from the ages of 26-35 years old with 71 victims (30,3%) in total. The majority of the domestic violence victims were female with the number of 200 people or 85% in total. Most victims of domestic violence occupied as private employees reaching 48,3% (113 people). The most common form of domestic violence was physical abuse within the number of 217 incidence (91,56%) with the most common types of wounds being contusions of 198 cases (61.1%). Domestic violence victims’ parts of injury mostly happened in the facial region in a total of 198 cases (31%). The classification of domestic violence was recorded as minor injury of 216 cases (92%). However, from 2018-2022 domestic violence incidence, 158 domestic violence cases (68%) did not have a post mortem request form. Conclusion : The characteristics of victims of domestic violence in RSUP Dr. Kariadi Semarang, the highest incidence in 2018 with the characteristics most victims from the age group 26 – 35 years, female, with work as a private employees. The most frequent violence was physical violence, with bruising wounds and wound locations on the facial region, as well as minor wounds. Most of the recorded cases were not accompanied by a a post mortem request letter. Keywords: Characteristics, Domestic Violence Victims, Domestic Violence.